Menentukan Harga Jual Mobil Bekas Menggunakan Fuzzy Logic Metode Sugeno - Ekawati, Nia; Salamena, Alvin Piterson (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2022)
Automotive companies are currently quite common in every country, one of which is Japan. Following this technology, Indonesia has begun to develop automotive production with the city car concept. The car produced in Indonesia is named Agya which is taken from the Sanskrit word which means "fast". Agya is produced by Astra, Toyota and Daihatsu companies. Based on these three companies, Astra chose Toyota, which took the car with the name Agya as the production name to be sold. Agya cars in Batam City can be found pretty much anywhere, such as on highways, malls, offices, airports and ports. Agya car sales increased in line with consumer demand, because the city car was included in the inexpensive selling price category, compared to other city cars whose names are well known overseas or domestically. There are some users who already own Agya cars and resell them, of course there could be potential for the process of selling used Agya brand cars. Buying a used car, of course, has a lot to pay attention to, even if the car has only been used, for example, for about 3 months. The process that must be considered if we want to buy a used car is the condition of the engine, interior condition, and exterior condition. However, what is more to be considered is whether the price of the used car is in accordance with the condition of the car.